Rocking in my school shoes ebook - Litwin, Eric (Pete the Cat., 2011)
Time to head back to school with this bestselling groovy Pete the Cat book! Pete the Cat is rocking in his school shoes. Pete discovers the library, the lunch room, the playground, and lots of other cool places at school. And no matter where he goes, Pete never stops moving and grooving and singing his song...because it's all good. The fun never stops—download the free groovin' song. Don't miss Pete's other adventures, including Pete the Cat: I Love My White Shoes, Pete the Cat and His Four Groovy Buttons, Pete the Cat Saves Christmas, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the New Guy, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, Pete the Cat and the Perfect Pizza Party, and Pete the Cat: Crayons Rock!